Improving performance and reducing cost in buyer-supplier relationships: The role of justice in curtailing opportunism - Luo, Yadong; Liu, Y.; Yang, Q.; Maksimov, V.; Hou, J. (Elsevier, 2015)
Building on social exchange theory, we study the role of justice perceptions in curtailing opportunism and, in turn, improving performance and reducing governance cost in buyer-supplier relationships. Our analysis of 225 dyads in the Chinese home appliance industry indicates that distributive justice is negatively linked to strong form opportunism, whereas procedural justice and interactional justice perceptions are negatively related to weak form opportunism. Additionally, while relationship performance is equally reduced by both forms of opportunism, governance cost increases significantly more with strong form opportunism. We conclude that preserving the formal structure of the exchange through distributive justice and the informal mechanisms of interaction through procedural justice and interactional justice is important in enhancing performance and reducing cost. We caution that we view the role of organizational justice as complementary to economic forces such as contractual and managerial governance.